VD_FINDINFO AI 320/08 - 202/2010 vom 27. Mai 2010 - VD Tribunal cantonal (2010)
PRESTATION D'ASSURANCEAI, FORCE PROBANTE | 1 LAI, 28 al. 1 LAI, 69 al. 1bis LAI, 16 LPGA, 60 al. 1 LPGA, 61 let. g LPGA, 7 al. 1 LPGA, 7 al. 2 LPGA, 8 LPGA, 117 al. 1 LPA-VD, 2 LPA-VD, 30 al. 1 LPA-VD, 30 al. 2 LPA-VD, 49 al. 1 LPA-VD, 55 al. 1 LPA-VD, 93 al. 1 let. a LPA-VD